2002
DOI: 10.1080/1065657x.2002.10702075
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Population Dynamics and Enzyme Activities During Composting

Abstract: The changes in population size of different microbial groups (total aerobic heterotrophs, actinomycetes, fungi, fecal coliforms, ammonium-and nitrite-oxidizing bacteria, and denitrifying bacteria) and the activities of 19 different enzymes (three phosphatases, threeesterases, two proteases, three amino-peptidases, and eight glycosyl-hydrolases) were examined during cocomposting of poultry litter (a mixture of poultry manure, waste feed, feathers, and wood shavings) and yard trimmings (a mixture of grass clippi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(109 citation statements)
references
References 28 publications
3
91
1
1
Order By: Relevance
“…Although the elimination of pathogens by composting has been well documented (Deportes et al, 1998;Tiquia et al, 2002;Larney et al, 2003), composting times and temperatures required to achieve elimination or reduction of the number of E. coli vary widely. Turner (2002) demonstrated inactivation of E. coli in farmyard manure, pig feces, and cereal straw already after 2h at 55 o C. In contrast, Lau and Ingham (2001) reported that E. coli could be cultured from bovine manure kept for 19 weeks at 21 o C. In the present study, E. coli could be cultured at every condition tested after up to 120 days, however the non-O157 STEC-stx2-gene strains were not found after 30 days, indicating that competition among the bacteria associated with the temperature seem to be very important aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Although the elimination of pathogens by composting has been well documented (Deportes et al, 1998;Tiquia et al, 2002;Larney et al, 2003), composting times and temperatures required to achieve elimination or reduction of the number of E. coli vary widely. Turner (2002) demonstrated inactivation of E. coli in farmyard manure, pig feces, and cereal straw already after 2h at 55 o C. In contrast, Lau and Ingham (2001) reported that E. coli could be cultured from bovine manure kept for 19 weeks at 21 o C. In the present study, E. coli could be cultured at every condition tested after up to 120 days, however the non-O157 STEC-stx2-gene strains were not found after 30 days, indicating that competition among the bacteria associated with the temperature seem to be very important aspects.…”
Section: Discussionmentioning
confidence: 99%
“…There is abundant literature related to different aspects of composting, such as microbiological studies (Tiquia et al, 2002), changes of chemical composition (Pichler et al, 2000), technical and operational considerations (Wong and Fang, 2000) or even some aspects of process modeling such as kinetics (López-Zavala et al, 2004). However, there is scarce information about the prediction of temperature profiles in composting processes, especially at full-scale.…”
Section: Introductionmentioning
confidence: 99%
“…It was accompanied by the occurrence of the peak spectrum characteristic for cellulose (1317 cm −1 ). Biodegradation of lignocellulose (derived from the plant filler) of the composites results from collaboration of some fungi, actinomycetes and bacteria [48,[71][72][73]. The observed differences can be indicative for different proportions of cellulolytic and ligninolytic microorganisms which have the ability of decomposing resin acids in both substrates.…”
Section: Composting Of Pehd Composites With Pine Needles In Forest Comentioning
confidence: 99%